Student Error Analysis In The Experimental Stage Of A Virtual Laboratory As Seen In The Skills Of Science Process: A Literature Review - Alpina Pebrianti; Heni Yulianti; Handini Handini (Indonesian Journal of Applied Science and Technology, 2024)
This research is motivated by the importance of science process skills (SPS) in physics learning, as well as the increasing use of virtual laboratories that have not fully revealed the types of student errors in the experimental stage. The purpose of this paper is to analyze the forms of student errors in the experimental stage in virtual laboratories in terms of science process skills through a literature review. The method used is a literature review of 15 relevant scientific articles. Data analysis was carried out using content analysis techniques. The results of the study indicate that virtual laboratories are effective in improving SPS, but student errors still predominantly occur in the data interpretation and concept application stages. These errors are influenced by low conceptual understanding, lack of practical experience, and limited guidance. This study concludes that a more targeted learning strategy is needed to minimize student errors in the use of virtual laboratories.